Impact of Nutritional Stress on Honeybee Gut Microbiota, Immunity, and Nosema ceranae Infection - Castelli, L. (2020)
Honeybees are important pollinators, having an essential role in the ecology of natural and agricultural environments. Honeybee colony losses episodes reported worldwide and have been associated with different pests and pathogens, pesticide exposure, and nutritional stress. This nutritional stress is related to the increase in monoculture areas which leads to a reduction of pollen availability and diversity. In this study, we examined whether nutritional stress affects honeybee gut microbiota, bee immunity, and infection by Nosema ceranae, under laboratory conditions. Consumption of Eucalyptus grandis pollen was used as a nutritionally poor-quality diet to study nutritional stress, in contraposition to the consumption of polyfloral pollen. Honeybees feed with Eucalyptus grandis pollen showed a lower abundance of Lactobacillus mellifer and Lactobacillus apis (Firm-4 and Firm-5, respectively) and Bifidobacterium spp. and a higher abundance of Bartonella apis, than honeybees fed with polyfloral pollen. Besides the impact of nutritional stress on honeybee microbiota, it also decreased the expression levels of vitellogenin and genes associated to immunity (glucose oxidase, hymenoptaecin and lysozyme). Finally, Eucalyptus grandis pollen favored the multiplication of Nosema ceranae. These results show that nutritional stress impacts the honeybee gut microbiota, having consequences on honeybee immunity and pathogen development. Those results may be useful to understand the influence of modern agriculture on honeybee health.